Superior vena cava syndrome resembling recurrent Quincke’s oedema. Case report - Pająk-Grot, Magda; Kozłowska-Murawska, Jolanta; Siwicka, Maria (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Superior vena cava syndrome (SVCS) is a complex of symptoms of different aetiology, characterized by facial oedema, cyanosis, phlebectasia of the upper half of the chest and glottis oedema. Objective. To present a case of a woman with symptoms and medical history suggesting recurrent Quincke's oedema of drug-induced aetiology, who was finally diagnosed with SVCS due to ongoing pathology in the mediastinum. Case report. We present a case of a 54-year old woman who twice in the last year experienced oedema of the face, diagnosed and treated as recurrent Quincke's oedema of drug-induced aetiology. Allergic history was positive – allergy to grass pollen (hay fever), several episodes of contact allergy. The patient was treated with antihistamines and glucocorticosteroids. Due to the unsatisfactory response to treatment during the second episode of oedema, the presence of dilated veins on the chest and the exacerbation of dyspnoea, mainly in the morning, computed tomography (CT) of the chest was performed. The image showed the presence of pathological masses in the mediastinum and thrombi in the right atrium, the enlarged superior vena cava and the enlarged right jugular vein. The image suggested lymphoma and required further differentiation. Based on the result of CT of the chest, SVCS was diagnosed. Conclusions. The presented case of the patient with face swelling diagnosed as recurrent Quincke’s oedema, with seemingly obvious drug-inducted aetiology, demonstrates the necessity of careful observation of the patient and reported symptoms. It also reflects the diagnostic difficulties, because many conditions may give cutaneous reactions superficially resembling angioedema.